The Relationship Between Nurse Burnout and the Implementation of Patient Safety Goals: A Cross-Sectional Study - Panjaitan, Jismer; Linawati Togatorop; Anastasia, Cahaya Artha (Lembaga Chakra Brahmanda Lentera (Chakra Brahmanda Lentera Institute) [CANDLE], 2025)
Background: Nurse burnout is a persistent challenge in hospital settings and has been associated with compromised patient safety performance. Although previous studies have examined burnout and general safety outcomes, empirical evidence directly linking nurse burnout to the implementation of standardized Patient Safety Goals remains limited, particularly in low- and middle-income country contexts. Therefore, this study aimed to examine the relationship between nurse burnout levels and the implementation of patient safety goals among hospital nurses in Indonesia. Methods: A quantitative cross-sectional correlational study was conducted in October 2025. The study involved 97 registered nurses providing direct patient care, selected using purposive sampling. Inclusion criteria were nurses with a minimum of six months of work experience, while nurses in managerial positions or on leave were excluded. Nurse burnout (independent variable) was measured using the Maslach Burnout Inventory, and patient safety goal implementation (dependent variable) was assessed using a structured observation checklist based on World Health Organization and Indonesian Ministry of Health indicators. Data were collected anonymously following ethical approval and informed consent. Statistical analysis was performed using Spearman’s rank correlation test. This study followed the STROBE guidelines for reporting cross-sectional studies. Result: Most participants were female (86.6%) and aged 25–35 years (75.3%). Moderate burnout levels were reported by 58.8% of nurses, while 61.9% demonstrated good implementation of patient safety goals. A statistically significant correlation was identified between nurse burnout and patient safety goal implementation (r = 0.456; p < 0.001), indicating that higher burnout levels were associated with lower adherence to patient safety practices. Conclusion: Nurse burnout is significantly associated with the implementation of patient safety goals, indicating that nurses’ psychological well-being plays a critical role in ensuring safe care delivery. These findings highlight the need for organizational and psychosocial interventions targeting burnout reduction as an integral component of patient safety improvement strategies.